Access to Cyclic β‐Amino Acids by Amine‐Catalyzed Enantioselective Addition of the γ‐Carbon Atoms of α, β‐Unsaturated Imines to Enals. (23rd October 2019) - Luo, Guoyong; Huang, Zhijian; Zhuo, Shitian; Mou, Chengli; Wu, Jian; Jin, Zhichao; Chi, Yonggui Robin
Abstract: Disclosed herein is a new catalytic approach for an efficient access to cyclic β‐amino acids widely found in bioactive small molecules and peptidic foldamers. Our method involves addition of the remote γ‐carbon atoms of α, β‐unsaturated imines to enals by iminium organic catalysis. This highly chemo‐ and stereo‐selective reaction affords cyclic β‐amino aldehydes that can be converted to amino acids bearing quaternary stereocenters with exceptional optical purities. Our study demonstrates the unique power of organic catalytic remote carbon reactions in rapid synthesis of functional molecules. Abstract : So fern und doch so nah : Die direkte vinyloge Michael‐Addition des γ‐Kohlenstoffatoms α, β‐ungesättigter Imine an Enale wird durch Iminium‐Organokatalyse realisiert. Der Ansatz liefert einen schnellen Zugang zu enantiomerenreinen cyclischen Aminosäuren.